Study on the evolution of the traditional Chinese Medicine syndromes of primary nephrotic syndrome treated with rituximab in children and the prognosis - Ai Yi-ying; Wu Rui-bo; Wen Zi-long; Xu Kai-si (Linchuang shenzangbing zazhi)
ObjectiveTo prospectively observe changes in the traditional Chinese medicine （TCM） syndromes in children with primary nephrotic syndrome（PNS） before and after the rituximab （RTX） treatment， thus summarizing evolution patterns and prognostic impact of TCM syndromes types.MethodEighty-nine PNS children treated with RTX at pediatric inpatient department of Guangdong Provincial Hospital of Chinese Medicine from Jan 2023 to Dec 2023 were included. General information and TCM syndrome data before and after RTX treatment were collected via a TCM syndrome observation form. TCM syndrome differentiation was performed using form-recorded data. Data on TCM syndrome types （days 0， 30， and 60） and 6-month recurrence were entered into an Access database. Statistical analysis of the data was performed using SPSS 26.0.ResultsFor deficiency syndromes， pre-treatment dominant types on day 0 were dominantly the lung-spleen Qi deficiency （37.1%） and spleen-kidney Yang deficiency （57.3%）. At 30 days post-treatment， the proportions of liver-kidney Yin deficiency rose to 42.7% and Qi-Yin deficiency emerged （12.4%）. By day 60， the proportions of liver-kidney Yin deficiency （51.7%） and Qi-Yin deficiency （15.7%） further increased， with the lung-spleen Qi deficiency （12.4%） and spleen-kidney Yang deficiency （20.2%） continuing to decline. For excess syndromes， pre-treatment dominant concurrent syndrome on day 0 was water-dampness （32.6%）， followed by blood stasis （24.7%） and damp-turbidity （21.3%）. At 30 days post-treatment， wind pathogen （16.9%） became the most common concurrent syndrome. By day 60， external wind （21.3%）， blood stasis （18.0%）， and damp-heat （16.9%） were the leading concurrent syndromes. Significant differences existed in deficiency/empirical syndrome distributions across time points （P<0.05）. The liver-kidney Yin deficiency syndrome on day 30 significantly influenced the recurrence of PNS within 3-6 months（OR=0.058， 95% CI： 0.07-0.491， P=0.009<0.05）.ConclusionThere is a certain pattern in the evolution of TCM syndromes in children with PNS after RTX treatment. Pre-treatment dominant deficiencies are mainly the spleen-kidney Yang deficiency and lung-spleen Qi deficiency. At post-treatment， liver-kidney Yin deficiency and Qi-Yin dual deficiency increased significantly. Prognostically， the syndrome of liver-kidney Yin deficiency at day 30 post-treatment predicts a reduced recurrence risk of PNS at 3-6 months in children.